The Effect of the Implementation of Permenkes No. 72 of 2016 on the Management of Pharmaceutical Preparations and the Role of Pharmaceutical Personnel on Service Quality (Research at Class D Hospital in Bekasi City) - Ika Ismayani; Sampurno Sampurno; Lies Putriana (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
One of the health services in the hospital is a pharmacy installation, while the definition of a pharmacy installation is a functional implementing unit that organizes all pharmaceutical service activities in the hospital. Pharmaceutical Services is a direct and responsible service to patients related to pharmaceutical preparations with the aim of achieving definite results to improve the patient's quality of life. The service standard is contained in the Regulation of the Minister of Health no. 72 of 2016 concerning Pharmaceutical Service Standards in Hospitals which aims to improve the quality of pharmaceutical services, guarantee legal certainty for pharmaceutical personnel, and protect patients and the public from irrational drug use in the framework of patient safety. The regulation of service standards is contained in Minister of Health Regulation No. 72 of 2016. covers management standards for pharmaceutical preparations, medical devices and consumable medical materials as well as clinical pharmacy services. With the implementation of Permenkes No. 72 of 2016 is expected to be able to improve service quality. Factors that play a role in improving service quality include the management of pharmaceutical preparations and the role of pharmaceutical staff. This research is a quantitative research using survey method. The population in this study were pharmaceutical supply managers and patients who came to Class D hospitals in Bantar Gebang, Jatisampurna and Pondok Gede. The results showed that there was an effect of the implementation of Permenkes 72 of 2016 on the quality of pharmaceutical services in Class D Hospitals in Bekasi City, with the involvement of pharmaceutical staff in the management of pharmaceutical preparations from the process of selecting, planning needs, procurement, receiving, storage, distribution, destruction and withdrawal, control, and administration. There is an influence of the management of pharmaceutical preparations on the quality of pharmaceutical services in Class D Hospitals in Bekasi City, as seen from the dimensions of trust and empathy that meet expectations in Class D Hospitals Jatisampurna.